A database for screening and registering late onset Pompe disease in Turkey - KAHRAMAN KOYTAK, PINAR (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
The aim of this study was to search for the frequency of late onset Pompe disease (LOPD) among patients who had a myopathy with unknown diagnosis registered in the pre-diagnostic part of a novel registry for LOPD within a collaborative study of neurologists working throughout Turkey. Included in the study were 350 patients older than 18 years who have a myopathic syndrome without a proven diagnosis by serum creatine kinase (CK) levels, electrodiagnostic studies, and/or muscle pathology, and/or genetic tests for myopathies other than LOPD. Acid alpha glucosidase (GAA) in dried blood spot was measured in each patient at two different university laboratories. LOPD was confirmed by mutation analysis in patients with decreased GAA levels from either both or one of the laboratories. Pre-diagnostic data, recorded by 45 investigators from 32 centers on 350 patients revealed low GAA levels in a total of 21 patients; from both laboratories in 6 and from either one of the laboratories in 15. Among them, genetic testing proved LOPD in 3 of 6 patients and 1 of 15 patients with decreased GAA levels from both or one of the laboratories respectively. Registry was transferred to Turkish Neurological Association after completion of the study for possible future use and development. Our collaborative study enabled collection of a considerable amount of data on the registry in a short time. GAA levels by dried blood spot even from two different laboratories in the same patient may not prove LOPD. LOPD seemed to be rarer in Turkey than in Europe. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: LOPD; Registry; Limb girdle muscle weakness; Acid alpha glucosidase; GIRDLE MUSCULAR-DYSTROPHY; HYPERCKEMIA; PREVALENCE; MYOPATHIES; COHORT